2021
DOI: 10.1073/pnas.2105730118
|View full text |Cite
|
Sign up to set email alerts
|

Altered effective connectivity in sensorimotor cortices is a signature of severity and clinical course in depression

Abstract: Functional neuroimaging research on depression has traditionally targeted neural networks associated with the psychological aspects of depression. In this study, instead, we focus on alterations of sensorimotor function in depression. We used resting-state functional MRI data and dynamic causal modeling (DCM) to assess the hypothesis that depression is associated with aberrant effective connectivity within and between key regions in the sensorimotor hierarchy. Using hierarchical modeling of between-subject eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 119 publications
2
16
0
Order By: Relevance
“…Functional connectivity studies support this view, as cognitive control networks including the LPFC are observed less frequently in patients remitted from MDD ( Figueroa et al, 2019 ), whereas non-relapsers tend to show increased connectivity of the LPFC with executive control regions following antidepressant discontinuation ( Berwian et al, 2020 ). While less often the focus of neuroimaging research, emerging mechanistic accounts of depression have also implicated sensorimotor dysfunction a reliable correlate of symptom burden ( Ray et al, 2021 ), which is consistent with established findings linking experiential avoidance to depression vulnerability ( Barnhofer et al, 2014 , Panayiotou et al, 2015 ). The present findings affirm the role of sensory deactivation in characterizing depression relapse vulnerability, broadening accounts of depression vulnerability to also sensorimotor deactivation as a contributing vulnerability biomarker.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Functional connectivity studies support this view, as cognitive control networks including the LPFC are observed less frequently in patients remitted from MDD ( Figueroa et al, 2019 ), whereas non-relapsers tend to show increased connectivity of the LPFC with executive control regions following antidepressant discontinuation ( Berwian et al, 2020 ). While less often the focus of neuroimaging research, emerging mechanistic accounts of depression have also implicated sensorimotor dysfunction a reliable correlate of symptom burden ( Ray et al, 2021 ), which is consistent with established findings linking experiential avoidance to depression vulnerability ( Barnhofer et al, 2014 , Panayiotou et al, 2015 ). The present findings affirm the role of sensory deactivation in characterizing depression relapse vulnerability, broadening accounts of depression vulnerability to also sensorimotor deactivation as a contributing vulnerability biomarker.…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, in one of the few prospective neuroimaging studies of MDD recurrence, both PFC activation and sensory deactivation were associated with new MDD episodes over a subsequent 18-month follow-up ( Farb et al, 2011 ). In parallel, emerging connectivity studies of depression suggest that abnormal sensorimotor connectivity may be a powerful but overlooked feature of depressive symptom burden and treatment response ( Ray et al, 2021 ). While small sample sizes limit the generalizability of regional findings, such studies provide initial evidence for characterizing MDD relapse vulnerability as an over-reliance on cognitive elaboration to the detriment of sensory integration.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have examined rsfMRI networks in both depressed patients and animal models, yielding highly quantitative and objective measurements that are of theranostic utility ( 2 , 32 , 38 , 39 ). However, the relationship between astrocyte dysfunction and these rsfMRI measurements in depression remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The brain regions with notably altered rsfMRI connectivity in MDD patients and Itpr2 −/− mice can be associated with depression ( 2 , 13 , 14 , 38 , 42 ), such as mPFC, TH, Str, AMY, SsCx, VCx, SC, Hb, DRN, and Ant ( Figs. 1 and 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, network rigidity related to poorer resilience among AD-prone adolescents. Anchored in VIS areas of greater GABA, relative to GLU, receptor density, this profile reaffirmed the importance of externally oriented processing systems to MDD pathology (e.g., [68]), as well as the role of E/I balance in supporting functional network development (69). It also underscored the importance of conducting more targeted, neurotransmitter system-specific investigations into the relationships among AD/MDD risk, resilience and incentive processing.…”
Section: Discussionmentioning
confidence: 59%